FACTORS AFFECTING FINANCIAL DISTRESS IN MANUFACTURING COMPANIES LISTED ON IDX - Rahayuningtyas, Putri; Yanti, Yanti (Graduate Program of Universitas Tarumanagara, 2023)
This study empirically examines the factors influencing financial distress from 2018-2020. The independent variables used in this study are profitability, liquidity, sales growth, firm size, and firm activities. This study uses quantitative research methods with secondary data obtained from the annual financial statements of manufacturing companies listed on the BEI. There are 102 data from 64 companies selected as research samples based on the purposive sampling method. The data processing in this study was tested using the EViews 12. The results of the regression test showed that company size had a negative and significant effect on financial distress, while profitability and liquidity had a significant positive effect on financial distress and sales growth and activity had no effect on financial distress.